(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2024)
Utilization of fishery products by the fishery industry is processed into processed products besides functioning to extend shelf life as well as improving taste, making it easier for consumption (ready to serve), facilitating handling and packaging for marketing. This study aims to determine the percentage (%) of raw materials used to make canned fish as the expected main product. The study used the experimental treatment method on the research object, the type and size of fish raw materials to make canned fish as the main product, with 15 repetitions. Observation and direct measurement at the research location, by following all production processes from receiving raw materials to the main product, calculating the amount of canned fish products (kg). The results showed that the overall standard recovery (yield) of white meat from the amount of raw materials used, first the calculation of the recovery (yield) per tail was summed into one called the recovery mix standard. The research standard recovery mix rate determined by the company reached 38.07%. The average percentage of canned fish meat from the research results reached 35.81% of the fish raw materials used. The average percentage value or recovery mix standard has not been achieved, due to the different sizes and weights of fish used in processing.